Asymmetrical penetration of microwave in a conducting media and determination of microwave conductivity for very thin samples using electron spin resonance - Seridonio, A. C.; Walmsley, L. (Elsevier B.V., 2001)
Dyson's theory of conduction electron spin resonance (CESR) has been used in the limit d less than or equal to delta (d being the thickness of the sample and delta the skin depth of the microwave field) to obtain the microwave conductivity from the (A/B) ratio of the CESR absorbed power derivative. In this work we calculate the CESR absorbed power derivative using Kaplan's approach and show that the (A/B) ratio can be enhanced if asymmetrical penetration of microwave is used, which means that the microwave field enters into the sample from one of the faces. Therefore, the determination of the microwave conductivity from the (A/B) ratio of the CESR line can be performed for thinner samples. Experimentally, asymmetrical penetration can be obtained if one of the sample's faces is covered with a thin gold layer. The determination of microwave conductivity in conducting polymers films is among the possible applications of this method. (C) 2001 Elsevier B.V. Ltd. All rights reserved.
Keywords: thin films; electrical conductivity